PENGARUH STRUKTUR MODAL TERHADAP RENTABILITAS PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muliana Muliana; Maryana Maryana (LPPM STIE Lhokseumawe, 2017)
Purpose of research is earning writer to tell as according to the problem is to know how big governmental internal control system influence had an effect on to efficient and management effectiveness of finance in Local Government Kabupaten Aceh Utara. Data applied in the form of primary data obtained collected or from direct observation of all officer Dinas Pendapatan and Pengelolaan Keuangan Kabupaten Aceh Utara through a questionnaire. Data processing is done with help of equation model of simple regression that analyzes using program SPSS. The result of research indicates that governmental internal control system had an effect on significant to efficient and management effectivity of finance at Dinas Pendapatan and Pengelolaan Keuangan Daerah Kabupaten Aceh Utara. Efesiensi and management effectivity of finance at Dinas Pendapatan and Pengelolaan Keuangan Daerah Kabupaten Aceh Utara can be explained by government internal control system applied, governmental internal control system excelsior hence will be followed excelsior also efficiency and management effectivity of finance area.